The Effect Of Servant Leadership, Organizational Culture On Organizational Citizenship Behavior, And Motivation As A Mediating Variable In Hkbp Jakarta District - Hutagaol, Eirene Lestari P (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to test the direct and indirect effects of Servant Leadership, Organizational Culture on Organizational Citizenship Behavior in HKBP Jakarta District. In addition, this study also aims to examine the influence of motivational mediation variables on the relationship between servant leadership and organizational culture with organizational citizenship behavior. This research was conducted on 436 church elders consisting of (treasurer, secretary and elders) in the Jakarta District HKBP. Research sampling using cluster random sampling method with data collection method using questionnaires. Data analysis was conducted using structural equation modeling (SEM) and using the SmartPLS 3.3.9 data processing program. The results showed that servant leadership and organizational culture have a direct and significant effect on organizational citizenship behavior. And through motivation is also able to mediate servant leadership and organizational culture on organizational citizenship behavior and has a significant influence